Understanding the Meaning of Triangular Shape in Mosque Architecture in Indonesia - Jamaludin, J.; Salura, Purnama (International Journal of Engineering and Technology, 2018)
This paper discuss the formal and symbolical meaning of triangular shape of contemporary mosque architecture in Indonesia, with case study the mosques designed by Ridwan Kamil in Jakarta and in rest area Km 88 toll road between Jakarta and Bandung. There was a question in the public whether the triangular shape was adequate to be used as a mosque building. This paper propose answers with the analitical descriptive to understand the symbolical meaning of triangle shape used Sundanese community culture, one of  Indonesian ethnics as representation. The paper used comparation and interpretation method to reveals the meaning of triangle shape in local culture and to find the connection to triangle shape in contemporary mosques architecture. The vernacular mosques in Indonesia known with their pyramid shape stacked roof with pointed roof in the peak. The pointed roof derived from the mountain that believed as the sacred place and used as symbol in the form of stacked roof of mosque. The finding of this paper is that triangular form can be accepted as mosque architectural form for the symbolical meaning derived from Sundanese culture. In the two mosques, this triangle shape enlarged and become praying room and as bridge to the God realm. The shape then achieved two purpose, as symbol of holy place and also fullfiled the function of praying room.